Secretor status and ankylosing spondylitis. - Pal, A; Hill, M; Wordsworth, P; Brown, M (1998)
OBJECTIVE: To assess the genetic association between secretor status and ankylosing spondylitis (AS). METHODS: A restriction digest method for determining secretor status was developed; 166 patients with AS and 216 healthy British white controls were typed for secretor status using this method. RESULTS: The frequency of nonsecretors among patients with AS (47/166, 28%) was not significantly different from controls (72/216, 33%). CONCLUSION: Secretor status does not influence susceptibility to AS.